The Substantial Role of Cell and Nanoparticle Surface Properties in the Antibacterial Potential of Spherical Silver Nanoparticles [Response to Letter] - Krychowiak-Maśnicka M; Wojciechowska WP; Bogaj K; Bielicka-Giełdoń A; Czechowska E; Ziąbka M; Narajczyk M; Kawiak A; Mazur T; Szafranek B; Królicka A (Nanotechnology, Science and Applications)
Marta Krychowiak-Maśnicka,1,* Weronika Paulina Wojciechowska,1,* Karolina Bogaj,1 Aleksandra Bielicka-Giełdoń,2 Ewa Czechowska,3 Magdalena Ziąbka,4 Magdalena Narajczyk,5 Anna Kawiak,6 Tomasz Mazur,7 Beata Szafranek,2 Aleksandra Królicka1 1University of Gdansk, Intercollegiate Faculty of Biotechnology, Laboratory of Biologically Active Compounds, Gdansk, Poland; 2University of Gdansk, Faculty of Chemistry, Gdansk, Poland; 3University of Gdansk, Intercollegiate Faculty of Biotechnology, Laboratory of Experimental and Translational Immunology, Gdansk, Poland; 4AGH University of Krakow, Faculty of Materials Science and Ceramics, Department of Ceramics and Refractories, Krakow, Poland; 5University of Gdansk, Faculty of Biology, Bioimaging Laboratory, Gdansk, Poland; 6University of Gdansk, Intercollegiate Faculty of Biotechnology, Laboratory of Plant Protection and Biotechnology, Gdansk, Poland; 7AGH University of Krakow, Academic Centre for Materials and Nanotechnology, Krakow, Poland*These authors contributed equally to this workCorrespondence: Marta Krychowiak-Maśnicka, Laboratory of Biologically Active Compounds, Intercollegiate Faculty of Biotechnology of the University of Gdansk and the Medical University of Gdansk, University of Gdansk, Abrahama 58, Gdansk, 80-307, Poland, Email marta.krychowiak@ug.edu.pl